The Najaf Environment Directorate Adopts the Strategic Option in Sustainable Development to compatible with Iraq’s Climate Change: Analysis Study for the opinions of members of the Environment Directorate - Al-Mousawi, Hiyam Hassan Zabr (The Arab Journal of Administration, 2024)
The purpose of this research is to understand the role of the adoption of the Directorate of Environment in Najaf in keeping pace with the strategic options for climate change by facilitating sustainable development/examining its analysis of the views of the Directorate’s members. This research builds on global metrics to measure research variables, including strategic options for climate change and sustainable development, and indicators are used to promote these concepts and focus on the Environment Directorate’s sample research. The problem of research was the following question: (What is the relationship between the nature of the Environment Directorate’s adoption and the strategic option to keep pace with climate change and sustainable development)? The research recommended that the relevant Environment Directorate should strengthen its staff’s strategic choices and keep abreast of climate change ravaging conservation through understanding sustainable development and renewable energy.